(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Panchvalkal is a combination of five astringent plants, these are Vata, Peepal, Udumbara, Parisha, Plaksha. Individual and combinations of drugs have Kashaya rasa (astringent) dominant and useful in the management of Vrana (Wounds) as well as Shotha (Inflammations). Panchvalakal is used in different forms, for instance, Kwath, ointment, and powder. Its formulation can prepare in oil for future prospective to add more medicinal value and improve its shelf life without any chemical preservative. The purpose of this study was to demonstrate the scientific proof of old literature and further evaluate the wound healing property of water extract of Panchvalkal and blend with Amaltas (Cassia fistula) and Neem (Azadirachta indica). Disc diffusion was adopted to assess antimicrobial activity against the range of standard antimicrobial agents. The results were promising that E.coli, S.aureus, P.areuginosa are sensitive to Panchvalkal kwath. This herbal medicine is able to prevent vaginitis and also cure it without any side effects. Aqueous extract of Panchvalkal by soxhlet method showed significant results against E.coli and S.aureus with an inhibition value of 22 mm and 20 mm in diameter respectively. The results were compared with results obtained from reference (standard) antibiotics, Ciprofloxacin (5mcg/disc), Ceftriaxone (30mcg/disc), and Streptomycin (10mcg/disc) that served as the reference for inhibition zone diameter.